Стратегия убеждения и тактики ее реализации в рекламных текстах о достопримечательностях Беларуси - Triguk, Marina (Acta Universitatis Lodziensis. Folia linguistica rossica, 2019)
The article analyzes the language of an advertising text in the context of selection of strategies and tactics of speech manipulation. In connection with the development of international tourism in Belarus, it is interesting to describe the strategy of persuasion and tactics of its implementation in advertising texts about Belarus’s popular destinations. The research employed the method of selective sampling, descriptive method, and stylistic method. The study describes the tactics of implementing the strategy of persuasion, establishes the linguistic means of implementing it and their pragmatic role. In conclusion, the author highlights the diversity of use of persuasion strategy tactics in advertising texts about Belarusian attractions. Multi-level language tools are used to implement the strategy with a view to influencing tourist consumers at logical and emotional levels and ensuring effective management of their opinion.